P213 Raised faecal calprotectin in inflammatory bowel disease (IBD) patients: 100% accurate or potential red herring?. (25th January 2019) - Christopher, B; Clifford, C; White, C; Anderson, E; Keohane, J; Sengupta, S
Abstract: Background: Faecal biomarkers of gastrointestinal inflammation have appeared in the past decade, of which calprotectin, a neutrophil cytosolic protein, has been studied the most. Faecal calprotectin (FC) is increasingly being used in clinical practice as surrogate marker for intestinal inflammation. A meta-analysis of prospective studies using suspected IBD patients found the pooled FC sensitivity and specificity to be 93% and 96%, respectively. Previous studies showed that several medications, dietary supplements, sampling time, pregnancy, and body mass index have been mentioned as confounding variables affecting results. Single FC measurement may not be sufficiently accurate to evaluate gastrointestinal symptoms, and different biomarkers such as albumin and C-reactive protein, disease activity indices such as Harvey–Bradshaw index and Mayo score with or without endoscopic investigation should be used to interpret the full clinical context. The primary study aim is to assess the prevalence of this subgroup cohort and assess sensitivity and specificity of FC in our department. This subgroup identification may have clinical impact on provision of colonoscopy service if statistically significant. Methods: This retrospective analysis study involved obtaining results of FC samples taken and correlate with colonoscopic and histological findings. The FC samples in our institution were processed in two external labs (Biomnis, Ireland, and Birmingham, UK). Results: Our study cohort involved 80 patients (43 females, 37 males). The median age was 44. There were 38 patients with Crohn's disease, 35 with ulcerative colitis, 5 indeterminate, and 2 newly diagnosed IBD. The FC range in our external lab (Biomnis) are subdivided into 3-negative for level <50 μg/g, between 50 and 200 grey zone, and >200 is positive whilst the laboratory in Birmingham used the cut-off FC level < 60 μg/g as negative. There were 64 patients (80%) who had raised FC results. Of these, 55 (86%) had findings of colitis on histology and 9 (14%) showed negative histology ( p = 0.01, CI 95%). There were 13 (16.3%) patients who had normal FC and had colonoscopy performed which showed colitis findings and confirmed histologically. There were 3 patients (3.7%) who had normal FC with no colitis evident endoscopically and histologically. Abstract P213 Faecal calprotectin results breakdown. Conclusions: Faecal calprotectin is utilised in IBD centres as surrogate markers and initial non-invasive screening for intestinal inflammation. The FC specificity and sensitivity is variable and the possibility of confounding variables and patients' factors should be taken into account when interpreting results. References 1. Van Rheenen PF, Van de Vijver E, Fidler V. Faecal calprotectin for screening of patients with suspected inflammatory bowel disease: diagnostic meta-analysis. BMJ 2010;341:c3369. 2. Grip O, Janciauskiene S, Bredberg A. Use of atorvastatin as an anti-inflammatory treatment in Crohn's disease. Br J Pharmacol 2008;155:1085–92. 3. Garg M, Rosella O, Lubel JS, et al. Association of circulating vitamin D concentrations with intestinal but not systemic inflammation in inflammatory bowel disease. Inflamm Bowel Dis 2013;19:2634–43. 4. Lasson A, Stotzer PO, Ohman L, et al. The intra-individual variability of faecal calprotectin: a prospective study in patients with active ulcerative colitis. J Crohns Colitis 2015;9:26–32. 5. Jost T, Lacroix C, Braegger C, et al. Stability of the maternal gut microbiota during late pregnancy and early lactation. Curr Microbiol 2014;68:419–27. 6. Agilli M, Aydin FN. Value of faecal calprotectin for inflammatory bowel disease at first presentation. J Crohn's Colitis 2015;9:591.